Contemporary management of breast cancer during pregnancy and subsequent lactation in a multicenter cohort of young women with breast cancer. Issue 6 (18th July 2019) - Lee, Guek Eng; Rosenberg, Shoshana M; Mayer, Erica L; Borges, Virginia; Meyer, Meghan E; Schapira, Lidia; Come, Steven E; Partridge, Ann H
Abstract: The incidence of breast cancer diagnosed during pregnancy is increasing. We sought to characterize patient, treatment, pregnancy and lactation factors among young women with newly diagnosed breast cancer during pregnancy in a prospective cohort study. We identified all women who were pregnant when diagnosed with invasive breast cancer among those enrolled in the Young Women's Breast Cancer Study (NCT01468246), and collected details on pregnancy, birth and lactation from surveys, and treatment information medical record review. Of 1302 enrolled participants, 976 women with invasive breast cancer completed full baseline surveys, among whom 39 (4.0%) patients reported being pregnant at diagnosis. Median age at diagnosis was 34 years (range: 25‐40), with stage distribution: I, 28%; II, 44%; III, 23%; and IV, 5%. 74% of patients (29/39) had grade 3 tumors, 59% (23/39) ER‐positive, and 31% (12/39) HER2‐positive disease. 23 (59%) had surgery during pregnancy, 4 (17%) during the first trimester. Among the women who had surgery during pregnancy, 61% (14/23) underwent lumpectomy, 35% (8/23) unilateral, and 4% (1/23) bilateral mastectomy. All patients who had chemotherapy (51%, 20/39) received it in second and third trimesters, and had ACx4. There were 31 live births, 2 spontaneous, and 5 therapeutic abortions. Among live births, 16 (41%) were before 37 weeks of gestation. Three women reported breastfeeding. Within 6 months after delivery, comprehensive staging in 13 patients showed upstaging in four patients. In a contemporary cohort of young women with breast cancer, pregnancy at diagnosis is relatively uncommon. Treatment during pregnancy can generally be consistent with standard surgical and chemotherapy approaches, with attention to timing of therapies. Longer‐term outcomes including effects of some timing issues including delayed use of anti‐HER2 therapy on patient outcomes warrant further research.